Novel Cryptosporidium bat genotypes III and IV in bats from the USA and Czech Republic - Kváč, Martin; Hořická, Anna; Sak, Bohumil; Prediger, Jitka; Salát, Jiří; Širmarová, Jana; Bartonička, Tomáš; Clark, Mark; Chelladurai, Jeba Rose Jennifer Jesudoss; Gillam, Erin; McEvoy, John (Parasitology research, 2015)
Bats from the families Rhinolophidae (n = 90) and Vespertilionidae (n = 191) in the USA and Czech Republic were screened for the presence of Cryptosporidium by microscopic and molecular analysis of faecal samples collected from rectum of dissected animals and from the ground beneath roosting sites. Cryptosporidium oocysts were not detected in any of the 281 faecal specimens examined using the aniline-carbol-methyl violet staining method. Nested PCR amplification, sequencing and phylogenetic analysis of the small ribosomal subunit rRNA and actin genes were used to identify isolates and infer evolutionary relationships. Cryptosporidium parvum was identified in a western small-footed bat (Myotis ciliolabrum) from the USA and a common pipistrelle bats (Pipistrellus pipistrellus) from the Czech Republic. Two novel genotypes were identified and named Cryptosporidium bat genotype III and IV. Bat genotype III was found in two big brown bats (Eptesicus fuscus) from the USA. Bat genotype IV was detected in two common pipistrelle bats from the Czech Republic.
Keywords: Spojené státy americké; feces; Cryptosporidiosis; Phylogeny; kryptosporidióza; Molecular Sequence Data; molekulární sekvence - údaje; Cryptosporidium; Genotype; zvířata; United States; Feces; fylogeneze; Czech Republic; polymerázová řetězová reakce; Polymerase Chain Reaction; genotyp; Animals; Česká republika; Chiroptera